Psychological trajectories of mothers and fathers following their child's diagnosis of a life‐threatening illness or injury: A longitudinal investigation. Issue 10 (29th June 2019) - Darling, Simone J.; Hearps, Stephen J.C.; Muscara, Frank; McCarthy, Maria; Nicholson, Jan M.; Burke, Kylie; Dimovski, Anica; Anderson, Vicki
Abstract: Objective: Explore the mental health trajectories of parents following their child's life‐threatening illness/injury. Methods: Participants were 217 parents (mean age: 34.9–40.0; 66 fathers) of 165 children who presented to a tertiary hospital with a life‐threatening illness/injury. Parents completed questionnaires about their mental health and psychosocial stressors within 4 weeks of the child's illness/injury (T1), and 4 months (T2), 7 months (T3), and 19 months (T4) postdiagnosis. Results: For both mothers and fathers, mental health symptoms were elevated at diagnosis declining to normal levels by T3, with a pattern of increase at T4. Fathers demonstrated a faster decline in symptoms between T1 and T2, and fathers, but not mothers, experienced a relapse in depressive symptoms at T4. Fathers reported higher rates of work changes. Conclusions: These findings have important implications for the design and timing of parental interventions to support families of children with life‐threatening disease/injury.